BRICS Economic Cooperation Factors in Global Governance. Issue 1 (September 2020) - Li, Jingcheng; Pogodin, Sergey
Abstract: The formation of the BRICS cooperation mechanism was based on the political need to unite several rapidly growing countries. The process of its integration has shown the successful prospect of expanding the functions of the BRICS platform. This article studies the main factors of economic cooperation of the BRICS countries in the context of global governance and reforming the international financial and economic structure. The BRICS is one of the most important actors in the global governance of the 21st century, which brings together the most important forces of the developing countries in a new era; each of them is a regional power in Europe, Asia, South America and Africa. The study gives the thorough analysis of the national programs in the field of international economic activity, provides practical measures to resolve conflicts of interests among the BRICS countries and promote mutual understanding. The conclusion reveals the trend towards the formation of a multipolar system in international relations and the growing interdependence of the BRICS countries, noting the importance of economic integration and financial cooperation among these countries that is to get enhansed in order to defend together against the threat of unstable external environment and preserve national socio-economic development.